Pengembangan Modul Berbasis SETS (Science, Environment, Technology, And Society) Untuk Meningkatan Hasil Belajar Siswa Pada Materi Sistem Koloid Kelas XI IPA SMA - Ir. Luciyana Br Sirait; Lisnawaty Simatupang (Universitas Katolik Widya Karya Malang, 2023)
This study aims to determine the feasibility of SETS (Science, Environment, Technology, And Society) based modules on colloidal system, determine student learning outcomes after using SETS-based modules in learning and student responses to the modules. This study uses a 4-D development model consisting of define, design, development, and dissemination. This research was conducted at SMA Negeri 11 Medan which was carried out for 7 months. The feasibility of module was seen through a feasibility questionnaire for media and material experts based on the BSNP standard with a Likert scale of 1 to 5. Validation data obtained from media and material experts on SETS-based modules obtained an average percentage of 83.58% with the category valid/worthy. Student learning outcomes were obtained through the calculation of N-Gain test, which was equal to 0.74 in the high category and the average posttest score of students was 84.67. Student responses to the SETS-based module obtained an average percentage of 91.24% with a very high questionnaire interpretation. Based on the results obtained by the researcher, it can be concluded that this SETS-based module is appropriate for use in colloidal learning with a high student learning success rate and student responses that fall into very good criteria.